Barriers and drivers to COVID-19 vaccination among the migrant and non-migrant population in Germany, 2021 - Wulkotte, Elisa; Schmid-Küpke, Nora; Bozorgmehr, Kayvan; Razum, Oliver; Wichmann, Ole; Neufeind, Julia (European journal of public health, 2024)
During the Coronavirus Disease 2019 (COVID-19) pandemic, immunization programmes struggled to reach all population groups equally. While migrant groups face multiple barriers to health systems, including vaccination, little is known about their vaccine uptake.We conducted a cross-sectional telephone survey on adults with and without migration history in Germany to investigate barriers and drivers to COVID-19 vaccination (11 April 2021 to 18 December 2021). Interviews were conducted in six languages. We used logistic regression models and a mediation model to analyze the association between migration history and vaccine uptake. Furthermore, we determined the effect of psychological determinants (5C model) on vaccine uptake.The survey comprised 2039 individuals, including 1015 with migration history. Of these, 448 were interviews conducted in languages other than German. Individuals with migration history had a significantly lower vaccine uptake but, while still unvaccinated, had a higher intention to get vaccinated (P = 0.015) compared with those without migration history. The association between migration history and vaccine uptake was no longer significant when other factors were included in the regression model (odds ratio = 0.9; 95% confidence interval: 0.57-1.47). Socio-economic index, language skills and discrimination experience fully mediated this association. Among the psychological determinants, ‘higher confidence’ and ‘higher collective responsibility’ increased the chance of individuals with migration history to be vaccinated.Migration history alone cannot explain vaccine uptake; socio-economic index, language skills and discrimination experiences need to be considered. To achieve vaccine equity, future public health policy should aim to reduce relevant barriers through tailored interventions.
Gesehen am 07.06.2024